STUDENTS’ MASTERY IN USING CONTEXT CLUE IN READING TECHNICAL MATERIAL AT FOURTH SEMESTER STUDENTS OF STIBA PERSADA BUNDA PEKANBARU - Maspufah Maspufah (Journal of English Language and Education, 2017)
Technical materials refer to the material which is designed specifically to prepare a specialized career. This research is a descriptive research. The research conducted with an attempt to find out the students’ mastery in using context clue in reading technical material. The subject of the research was twenty students of fourth semester STIBA Persada Bunda Pekanbaru in academic year 2016/2017. The instrument used to collect the data was in the form of objective test. It was found that: (1) the students’ mastery in using synonym clue was in good category. They had problem in mastering synonym clue as they made mistake in taking the clue. (2) The students’ mastery in using antonym clue was in fair category. The problem occurred due to their vocabulary whereas the vocabulary used in technical material is high as it designed for native speaker. (3) The students’ mastery in using definition clue was in good category. The students were able to do the test because the clues were stated clearly. Besides, they also had sufficient experience and background knowledge to deduce meaning. Thus, it can be concluded that the students’ mastery in using context clue in reading technical marerial is needed to be improved because they still had limited vocabulary.